Core-Plus Mathematics - Hirsch, Christan R. (,McGraw-Hill, 2015)
In this course, you will learn important mathematics as you investigate and solve interesting prolems. You will develope the ability to reason and communicate about mathematics as you are actively engaged in understanding and applying mathematics.